2012
DOI: 10.1007/s00395-011-0242-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular risk in rats with primary renal dysfunction; mediating role for vascular endothelial function

Abstract: Primary chronic kidney disease is associated with high cardiovascular risk. However, the exact mechanisms behind this cardiorenal interaction remain unclear. We investigated the interaction between heart and kidneys in novel animal model for cardiorenal interaction. Normal Wistar rats and Munich Wistar Fromter rats, spontaneously developing renal dysfunction, were subjected to experimental myocardial infarction to induce cardiac dysfunction (CD) and combined cardiorenal dysfunction (CRD), respectively (N = 5–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…It has been demonstrated that RAS is important in the pathological heart hypertrophy [49], [50] that is counteracted by blocking AT 1 R [51] with simultaneous prevention of cardiac electric remodeling [52]. The view that kidney receptors are associated with heart receptors in the cardiac structural and electric remodeling receives further support from the observation that elimination of AT 1 R in mice reduces cardiac hypertrophy and the risk of hypertension [49], and also from the observation that primary renal dysfunction in rats is associated with an augmented risk of congestive cardiac failure in simultaneous alterations that constitute a cardiorenal syndrome [53].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that RAS is important in the pathological heart hypertrophy [49], [50] that is counteracted by blocking AT 1 R [51] with simultaneous prevention of cardiac electric remodeling [52]. The view that kidney receptors are associated with heart receptors in the cardiac structural and electric remodeling receives further support from the observation that elimination of AT 1 R in mice reduces cardiac hypertrophy and the risk of hypertension [49], and also from the observation that primary renal dysfunction in rats is associated with an augmented risk of congestive cardiac failure in simultaneous alterations that constitute a cardiorenal syndrome [53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies indicated that a multifactorial process leads to albuminuria to which multiple genetic loci are also contributing [8][9][10][11][12][13]. In addition, previous studies in MWF demonstrated an impaired endothelium-dependent relaxation in coronary microvessels [7] or aortas [16,17]. In this regard the Munich Wistar Frömter (MWF) rat model appears of interest to shed new light on this question.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that VEC injury could be caused by many substances: ox-LDL, Hcy, AngII, TNF-a and oxidative stress. VEC malfunction plays very important role in the pathogenesis of atherosclerosis, hypertension and diabetes (Falskov et al 2011;Szymanski et al 2012). Thus, the protection of VEC can prevent and treat several diseases.…”
Section: Introductionmentioning
confidence: 99%